A Clinical Audit on Management of Hypertension (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background : Hypertension is a major public health problem globally in both the developed and developing countries and it leads to cardiovascular diseases, stroke and kidney failure. The aim of this study was to identify the deficiency of management and to know the overall approach both by physician and cardiologist in daily routine OPD setting.Materials and methods : The patients’ mean age was 54.9±9.9years, 53.2% were male and 46.8% were female. In history taking important symptoms, family history and smoking history were poorly recorded (51.2%).Results : Of the hypertensive patients, 78.4% were well controlled (BP